KEBIJAKAN KEJAKSAAN AGUNG RI TENTANG PENGHAPUSAN TINDAK PIDANA KORUPSI DI BAWAH 50 JUTA DITINJAU DARI RESTORATIVE JUSTICE - Wahyu Danang Subiantoro; Hari Soeskandi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The Attorney General's Office of the Republic of Indonesia is a public prosecutor's office located in the capital city of the Republic of Indonesia, which is directly responsible under the president and whose jurisdiction covers the territory of the Republic of Indonesia. The Prosecutor's Office of the Republic of Indonesia is a state institution that exercises state power, especially in the field of prosecution. As a body that has the authority to enforce law and justice, the prosecutor's office is led by the Attorney General who is elected by and responsible to the president. The Prosecutor's Office as one of the state institutions in law enforcement is required to play a greater role in upholding the rule of law, protecting the public interest, upholding human rights, and eradicating corruption, collusion, and napotism. Restorative justice is one of the concepts of law enforcement in the settlement of cases that can be used as an instrument of recovery and has been implemented by the Supreme Court in the form of policy enforcement, but its implementation in the criminal justice system in Indonesia is still not optimal. Restorative justice is an alternative for solving criminal cases which in the mechanism of criminal justice procedures focus on punishment which is converted into a dialogue and/or mediation process involving the perpetrator and the victim to create an agreement on the settlement of criminal cases that is fair and balanced for the victims and the perpetrators themselves. . Meanwhile, according to the legal perspective, corruption is an act against the law with the intention of enriching oneself and/or other people, both individuals and corporations that can harm the state, such as bribery, extortion, embezzlement in office, fraudulent acts, conflicts of interest in procurement, and gratuities